Cloud Computing Alternative or the Future - Jiri Navratil; Sven Ubik; Pavel Pečiva (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
Modern IT intensively penetrates into various fields and changing them. We could see these trends in education, in medicine and in the culture. In last decade CESNET supported many partners from these fields. CESNET was also strongly involved in traditional form of IT, which is scientific calculation. Heavy users can use faster processors and new sophisticated applications which are able to process much bigger data. In the health care, special in the hospitals are used very sophisticated Information systems collecting complex data about all patients. Part of these IS are systems PACS (Picture Archiving and Communication Systems) which process graphical data from diagnostic devices as (CT, MRI, Digital X-ray, etc.). The museums and galleries were always important part of culture segment of society. Several years ago they had nothing special only couple of PCs. In last decade they started process of digitalization of theirs collections. All these examples demonstrate that computing facilities for such applications must be very powerful. The strong IT infrastructure is expensive and one important rule must be respected. IT infrastructure must be upgraded each 5 years to keep up with development. Such changes cost lot of money. Are the universities, hospitals, museums and other institutions which are fully dependent on state budget ready to do such innovation steps? The users need IT and they expect that level of services should grow. Everybody feel that there is no way back. Is there any economic way how to cover all these IT services? Today, there are many commercial companies which create business on this. They built huge data centers (DC) which offer sufficient computing capacity and data storage on commercial base for everybody in the form of cloud services. The commercial customers understand this situation very quickly because there are several big advantages. One of them is that customers do not need any initial investments for start. Another big advantage is flexibility and scalability which allow companies to overcome period of extreme load. Despite of visible benefits the academic world still hesitates, currently, there are many clouds available on different level and sizes. CESNET is a partner in the project “GEANT cloud Platform” which offers possibility to use the most advanced clouds.
Keywords: L82; 330; Cloud; Data Center DC; 4K video